A techno‐enviro‐economic multi‐objective framework for optimal sizing of a biomass/diesel generator‐driven hybrid energy system - Amir Akbarzadeh; Alireza Askarzadeh (IET Renewable Power Generation)
Abstract This article investigates multi‐objective size optimization of a hybrid energy system (HES) composed of biomass, photovoltaic (PV) and diesel generator considering technical, economic and environmental aspects. For this aim, two multi‐objective frameworks (techno‐economic and techno‐enviro‐economic) are developed where in the techno‐economic framework, total net present cost (TNPC) and loss of power supply probability (LPSP) are considered as the conflicting objectives. LPSP value is used as an index to measure the system reliability (by decrease of LPSP value, reliability will increase). In the techno‐enviro‐economic framework, net present cost of CO2 emission is also included in TNPC value. Furthermore, to determine the impact of biomass and diesel generator fuel costs on the Pareto front, a sensitivity analysis is conducted. Over the case study, simulated results show that in techno‐economic framework, at small values of LPSP, it is cost‐effective to use PV‐diesel rather than PV‐biomass system. In techno‐enviro‐economic framework, though at LPSP = 0, it is cost‐effective to use PV‐diesel system, in other levels of LPSP, it is desired to use PV‐biomass system.